565. MOVING FROM OPEN ESOPHAGECTOMY TO MINIMALLY INVASIVE ESOPHAGECTOMY: A PARADIGM SHIFT IN AN UPPER GASTROINTESTINAL CENTER. (24th September 2022) - Cheng, Shi Yu; Lim, Jolene; Voon, Kelvin
Abstract: Esophagectomy is a complex procedure that is traditionally associated with high morbidities. Minimally invasive esophagectomy (MIE) has the benefits of reduced post-op complications and improved quality of life in comparison to open esophagectomy (OE). This study aimed to compare the outcomes of MIE vs OE since the advocation of MIE as the standard approach in an upper gastrointestinal center. A retrospective review of prospectively collected data from the institutional online databank. OE was the main approach for esophageal cancer between year 2015 to 2017, while MIE was the standard approach in 2020 to 2021. Patient's demography, tumour's characteristics, operative approach, perioperative outcomes such as operation time, blood loss, post-op length of hospital stay, number of lymph node yield, post-op morbidities and mortality were compared between the OE (Jan 2015 – Dec 2017) and the MIE (Jan 2020 – Dec 2021) group. 28 patients were included in this study, 15 in the OE group while 13 in the MIE group. Mean age was similar in both groups (60.4vs59.4). 46.7% were of squamous cell carcinoma in the OE group vs 76.9% of adenocarcinoma in the MIE group. Ivor-Lewis approach was more common in the OE group (53.3%vs38.5%). MIE was associated with shorter mean operative time (489.38minutes vs 526minutes), less blood loss (110ml vs 250ml), shorter length of stay post-op (10.38days vs 24.67days) and higher number of lymph node yield (44vs31.67). Post-op morbidity was lower in MIE (30.7%vs73.3%) with Clavien-dindo grade-III and above complication rate of 7.69% vs 26.67%. 90-day mortality was 0 in the MIE vs 1 in the OE group. MIE was associated with shorter operative time, higher number of lymph node yield, reduced post-op morbidity, mortality and shorter post-operative hospital stay in patients with esophageal cancer. The encouraging results marked the paradigm shift from OE to MIE in our center.